A interpretação liberal de estado em Kant e o problema da resistência - Freitas, Valter (2014)
This dissertation aims to analyze how it presents the right of resistance in the thought of Kant. Thus, to study how Kant conceives the relationship between the citizen and the state, and as a liberal view harmonizes with the inability of the right of resistance, it is necessary to deeply understand his political theory. Thus, to argue that the German philosopher, the first function of the state is to protect freedom. From this perspective, the right takes odd function, for it is only by the rule of law can be free. Thus, Kant shows that the state of nature prevails only a temporary and transitional law and only with the passage of the state of nature to the civil state is that individuals have ensured, through state power, the coexistences freedoms according to a law universal. This transition occurs through a social contract in which individuals covenants its submission to the sovereign power, assuming this function representative of the general will and supreme guardian of freedom. Given this, one might conclude that it is a right of citizens to resist the state, violating the social contract, suppress individual freedoms? It would be reasonable to assume a right to rebellion against an unjust state? Kant writes that not. For it remains, in any case, the subject's duty of obedience to the state. Admit a right to resist the sovereign would undermine the foundations of the civil state that is embodied in the submission of the will to state power. A revolution means the destruction of the civil state and the return to the state of nature. So that adds a state for more authoritative as it may seem, it is even more fitting that the state of nature, where everything is insecure and reigns the greatest injustice. Concludes, then, that another hindrance in admitting the right of resistance is that no judge would be able to judge when the sovereign has violated the social contract and, therefore, would be authorized to rebellion. In fact, Kant still up against the right of resistance other arguments, such as the impossibility of malcontents to harmonize the maximum of their actions with the principle of publicity, and that the state is representative of the united will of the people, which would imply whoever attacks the Sovereign is attacking the will of the people own it represented. On one side, however, historically, Kant has been an enthusiastic supporter of the French Revolution, his political theory does not argue that revolutionary processes are able to bring qualitative changes. On the other hand, for most to consider the duty to obey an absolute duty, Kant stands as defender of free expression of thought and the ability of citizens to press their representatives in parliament, so that they operate gradual reforms in laws deemed unfair by the people. Therefore, it is perfectly possible to reconcile Kant's position of denial of the right of resistance to his liberal views, since it is only through the Empire of Law that freedom can exist under a universal law.